"No money exchanged hands, no bartering took place. But it's still local produce": Understanding local food systems in rural areas in the U.S. Heartland. (August 2020) - Hendrickson, Mary K.; Massengale, Sarah Hultine; Cantrell, Randolph
Abstract: Local food systems are frequently endorsed as an economic development strategy by local economic development practitioners serving rural communities and regions. However, from the limited data available, local food systems are more apparent and more fully developed in urban or peri-urban areas, while scholarship on rural food systems in and of themselves is lacking. What scholarship and data does exist suggests that people in rural places may participate in local food systems in different ways than what has been documented or observed in urban food systems, and that these systems may develop and spread in unique ways requiring new conceptions of intricate flows of locally produced foods, the social, ecological and economic benefits they may have, and the barriers and opportunities they present. We draw from three interrelated literatures – sustainable development, community capitals and rural wealth to conceptualize how the flow of locally produced foods through informal or undocumented channels can contribute to the sustainable development of rural places in the U.S. Through a series of 10 focus groups in the Midwest, we found that rural consumers participate in locally based food systems in distinctive ways that may bypass formal economic channels, such as self-provisioning; sharing and reciprocity; or informal cash or barter transactions. However, many of these forms of food system participation depend upon inclusion in social networks. We conclude that development of local food systems in rural areas will require renewed efforts to consider flows of community capitals from both informal and formal channels in the food system and investment in local food systems, not just in markets and regular economic exchanges. Moreover, as scholars we need to refine our understanding of the nature of food systems in rural areas, and develop new ways of thinking about how informal production-consumption arrangements can potentially contribute to rural development. Highlights: Rural people acquire local food through self-provisioning, sharing, reciprocity and informal arrangements. These forms of acquiring food depend upon specialized knowledge or inclusion in social networks. Such practices may be overlooked in building comprehensive rural wealth. Focusing on monetized impacts of local food systems may limit their application for rural development.